SELF-MANAGEMENT AS A MEANS OF PROFESSIONAL PERSONALITY DEVELOPMENT OF FUTURE TEACHERS - Dudnik, N.Yu. (Pedagogy of Higher and Secondary Education, 2022)
In this article is spoken about necessity of formation of students skills to self-management fo r their professional development in the pedagogical sphere.